Species richness, composition and microhabitat characteristics of non-volant terrestrial mammals in disturbed habitats - Wai, Leona; Bernard, Henry (Zenodo, 2019)
Description: A study on the small mammals communities was carried out in disturbed habitats aroundsabah, namely university malaysia sabah (ums), klias peat swamp forest reserve(klias), kawang forest reserve (kawang), kalabakan forest reserve (safe) and maliaubasin conservation area (maliau). the objectives were (1) to determine the speciesrichness and composition of non-volant small mammal communities in disturbedhabitats; (2) to characterize the microhabitat-use patterns of the non-volant smallmammal communities in disturbed habitats; and (3) to determine the microhabitatpreferences of the non-volant small mammal communities in disturbed habitats. the aimof this study was to investigate how the habitat disturbance affects the species richness,community compositions and microhabitat-use pattern of the small mammals. this studywas conducted from october 2014 to march 2015 with a total sampling effort of 540trap-nights. overall, 71 individuals representing 14 species were successfully caughtduring this study. the species richness peaked at safe, and then declined at the rest ofthe study sites. habitat variables analysis showed that all study sites were divided intothree distinctive groups in terms of habitat types. canonical discriminant functionanalysis were used to analyze the microhabitat preferences and use-pattern of smallmammals and results showed the preferences of small mammals towards shrub cover(rattus rattus and callosciurus notatus), litter cover (callosciurus prevostii and echinorexgymnurus) and herbs limber (tupaia gracilis). The locations of the traps have not been given longitute and latitute as there were set on animal trails approximately 20metres from one another. Project: This dataset was collected as part of the following SAFE research project: Species richness, composition and microhabitat characteristics of non-volant terrestrial mammals in disturbed habitats Funding: These data were collected as part of research funded by: Universiti Malaysia Sabah (Grant)This dataset is released under the CC-BY 4.0 licence, requiring that you cite the dataset in any outputs, but has the additional condition that you acknowledge the contribution of these funders in any outputs. Permits: These data were collected under permit from the following authorities:Sabah Biodiverstiy Council (Research licence NA) XML metadata: GEMINI compliant metadata for this dataset is available here Files: This consists of 1 file: Veg_Volent_mammals.xlsx Veg_Volent_mammals.xlsx This file contains dataset metadata and 2 data tables: Vegetation cover (described in worksheet Vegetation_cover)Description: The estimated canopy cover and percentage of ground cover of traps across disturbed habitatsNumber of fields: 19Number of data rows: 180Fields: Date : Date the vegetation cover was collected (Field type: Date) Location : Where data was collected (Field type: Location) Habitat_type : Habitat type (Field type: Categorical) Trap_station : Transect and trap number (Field type: ID) Canopy_cover : Percentage of canopy cover (Field type: Numeric) Canopy_height : Canopy height (Field type: Numeric) Herbs_Climber : Any climbers seen on trees for example vines and lianas (Field type: Numeric) Tree_GBH_>10CM : Tree girth at breast height of 10 cm (Field type: Numeric) Tree_GBH_>30CM : Tree girth at breast height of 30 cm (Field type: Numeric) Tree_GBH_>60CM : Tree girth at breast height of 60 cm (Field type: Numeric) Tree_GBH_>90CM : Tree girth at breast height of 90 cm (Field type: Numeric) Fallen_trees_bran : Percentage cover (Field type: Numeric) Bareground : Percentage cover (Field type: Numeric) Shrub : Percentage cover (Field type: Numeric) grass : Percentage cover (Field type: Numeric) Rock : Percentage cover (Field type: Numeric) Litter : Percentage cover (Field type: Numeric) Water : Percentage cover (Field type: Numeric) Twig : Percentage cover (Field type: Numeric) Non volent mammal abundance (described in worksheet Non_volent_mammals)Description: The abundance of non-volant terrestrails mammals caught across disturbed habitats. Growth and sex measurements takensNumber of fields: 17Number of data rows: 490Fields: Date : Date the vegetation cover was collected (Field type: Date) Location : Where data was collected (Field type: Location) Transect : Transect number (Field type: ID) Habitat : Habitat type (Field type: Categorical) Trap_station : Transect and trap number (Field type: ID) Species : Species of non volent mammals caught in trap (Field type: Taxa) Weight : Weight of caught non volent mammal (Field type: Numeric) Ear : Ear measurment of caught non volent mammal (Field type: Numeric) Hind_leg : Hind leg measurement of caught non-volent mammal (Field type: Numeric) Head_body : Head to body measurement of caught non volent mammal (Field type: Numeric) Tail : Tail length of caught non volent mammal (Field type: Numeric) Sex : Sex of caught non volent mammal (Field type: Categorical) Sexual_activity : Sexual maturity of caught non volent mammal (Field type: Categorical) Age : Age class of caught non volent mammal (Field type: Categorical) Trap_condition : Trap condition (Field type: Categorical) Trap_open_closed : Trap open or closed (Field type: Categorical) Bait : Bait taken or intact (Field type: Categorical) Date range: 2014-10-22 to 2015-03-30 Latitudinal extent: 4.5000 to 5.0700 Longitudinal extent: 116.7500 to 117.8200 Taxonomic coverage: All taxon names are validated against the GBIF backbone taxonomy. If a dataset uses a synonym, the accepted usage is shown followed by the dataset usage in brackets. Taxa that cannot be validated, including new species and other unknown taxa, morphospecies, functional groups and taxonomic levels not used in the GBIF backbone are shown in square brackets.Animalia - Chordata - - Mammalia - - - Erinaceomorpha - - - - Erinaceidae - - - - - Echinosorex - - - - - - Echinosorex gymnura - - - Rodentia - - - - Muridae - - - - - Lenothrix - - - - - - Lenothrix canus - - - - - Leopoldamys - - - - - - Leopoldamys sabanus - - - - - Maxomys - - - - - - Maxomys rajah - - - - - - Maxomys surifer - - - - - Niviventer - - - - - - Niviventer cremoriventer - - - - - Rattus - - - - - - Rattus rattus - - - - Sciuridae - - - - - Callosciurus - - - - - - Callosciurus adamsi - - - - - - Callosciurus notatus - - - - - - Callosciurus prevostii - - - - - Sundasciurus - - - - - - Sundasciurus lowii - - - Scandentia - - - - Tupaiidae - - - - - Tupaia - - - - - - Tupaia dorsalis - - - - - - Tupaia glis - - - - - - Tupaia gracilis